Massage for Dummies - Capellini, Steve (Hungry Minds, 2011)
Discover how to k nead your way to relaxation and wellness with this fun guide to the art of massage. With the help of 150 hand-on photos and illustrations, experts Steve Capellini and Michel Van Welden, show you, move by move, how to harness the healing power of touch. In no time you’ll: